Response and inaccuracy issues of sensors - Ashraful, Muhammad; Khan, Sheroz; Ibrahimy, Muhammad Ibn (IIUM Press, 2011)
In recent years, many kinds of sensors are used to get the response of various parameters such as pressure, speed, temperature, etc. Some parameters are highlighted in the following section by giving their measurement procedures